Influence of laser polarization on collective electron dynamics in ultraintense laser–foil interactions. (27th September 2016) - Gonzalez-Izquierdo, Bruno; Gray, Ross J.; King, Martin; Wilson, Robbie; Dance, Rachel J.; Powell, Haydn; MacLellan, David A.; McCreadie, John; Butler, Nicholas M. H.; Hawkes, Steve; Green, James S.; Murphy, Chris D.; et al.
Abstract : The collective response of electrons in an ultrathin foil target irradiated by an ultraintense ( 6× 10^20 W cm^-2 ) laser pulse is investigated experimentally and via 3D particle-in-cell simulations. It is shown that if the target is sufficiently thin that the laser induces significant radiation pressure, but not thin enough to become relativistically transparent to the laser light, the resulting relativistic electron beam is elliptical, with the major axis of the ellipse directed along the laser polarization axis. When the target thickness is decreased such that it becomes relativistically transparent early in the interaction with the laser pulse, diffraction of the transmitted laser light occurs through a so called 'relativistic plasma aperture', inducing structure in the spatial-intensity profile of the beam of energetic electrons. It is shown that the electron beam profile can be modified by variation of the target thickness and degree of ellipticity in the laser polarization.